Immune profiling in multiple sclerosis: a single-center study of 65 cytokines, chemokines, and related molecules in cerebrospinal fluid and serum - Berek, Klaus; Bauer, Angelika; Rudzki, Dagmar; Auer, Michael; Barket, Robert; Zinganell, Anne; Lerch, Magdalena; Hofer, Livia; Grams, Astrid; Poskaite, Paulina; Wurth, Sebastian; Berger, Thomas; et al. (Frontiers in Immunology, 2023)
Introduction The understanding of the pathophysiology of multiple sclerosis (MS) has evolved alongside the characterization of cytokines and chemokines in cerebrospinal fluid (CSF) and serum. However, the complex interplay of pro- and anti-inflammatory cytokines and chemokines in different body fluids in people with MS (pwMS) and their association with disease progression is still not well understood and needs further investigation. Therefore, the aim of this study was to profile a total of 65 cytokines, chemokines, and related molecules in paired serum and CSF samples of pwMS at disease onset. Methods Multiplex bead-based assays were performed and baseline routine laboratory diagnostics, magnetic resonance imaging (MRI), and clinical characteristics were assessed. Of 44 participants included, 40 had a relapsing–remitting disease course and four a primary progressive MS. Results There were 29 cytokines and chemokines that were significantly higher in CSF and 15 in serum. Statistically significant associations with moderate effect sizes were found for 34 of 65 analytes with sex, age, CSF, and MRI parameters and disease progression. Discussion In conclusion, this study provides data on the distribution of 65 different cytokines, chemokines, and related molecules in CSF and serum in newly diagnosed pwMS.